Marie Antoinette and the decline of French monarchy - Lotz, Nancy; Phillips, Carlene 1938- (Greensboro, NC : Morgan Reynolds Publishing, Inc., 2005)
Presents the life of Marie Antionette, covering her marriage at the age of fifteen to King Louis XVI, her life as wife and mother in the French court, and her courage in the final months before her death at the guillotine.
includes bibliographical references and index
10 years and up
Keywords: Marie Antoinette, Queen -- 1755-1793 -- Juvenile literature; Queens -- France -- Biography -- Juvenile literature; France -- History -- Revolution, 1789-1799